THE URGENCY OF INCLUSIVE EDUCATION IN THE 21ST CENTURY : OPPURTUNITIES, CHALLENGES, FUTURE AND RESEARCH RECOMMENDATIONS - Wasila, Nur Fatkhiya Warda; Imron, Ali; Juharyanto, Juharyanto (Universitas Negeri Surabaya, 2024)
Inclusive education in the 21st century presents significant opportunities and challenges alongside technological advancements and global social changes. This study aims to explore opportunities, challenges, and recommendations for future research in the implementation of inclusive education. The methodology employed in this research includes bibliometric analysis and a systematic literature review, utilizing Publish or Perish (PoP) and VOSviewer applications to process data retrieved from the Web of Science (WoS) database on inclusive education from 2021 to 2025. The research findings highlight three main aspects (1) opportunities can be leveraged to support the implementation of inclusive education in the 21st century, particularly in the context of globalization, digital transformation, and the post-COVID landscape; (2) challenges in achieving inclusive education in the 21st century, particularly in light of the pandemic’s impact; (3) strategies and research recommendations are needed to develop a more inclusive, adaptive, and sustainable education system for the future, especially with regard to fostering 21st-century skills for all learners.